2020
DOI: 10.1111/jcmm.15670
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR‐134‐5p induces calcium deposition by inhibiting histone deacetylase 5 in vascular smooth muscle cells

Abstract: Calcium deposition in vascular smooth muscle cells (VSMCs) is a form of ectopic ossification in blood vessels. It can result in rigidity of the vasculature and an increase in cardiac events. Here, we report that the microRNA miR‐134‐5p potentiates inorganic phosphate (Pi)‐induced calcium deposition in VSMCs by inhibiting histone deacetylase 5 (HDAC5). Using miRNA microarray analysis of Pi‐treated rat VSMCs, we first selected miR‐134‐5p for further evaluation. Quantitative RT‐PCR confirmed that miR‐134‐5p was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…miR-25 protects glucocorticoid-induced apoptotic process in VSMCs thereby reducing vascular calcification ( Zhang et al, 2019 ). miR-134-5p exacerbates vascular calcification by regulating the expression of histone deacetylase 5 in high phosphate conditions ( Choe et al, 2020b ). CircSmoc1-2 attenuates vascular calcification by regulating the miR-874-3p/Adam19 axis ( Ryu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-25 protects glucocorticoid-induced apoptotic process in VSMCs thereby reducing vascular calcification ( Zhang et al, 2019 ). miR-134-5p exacerbates vascular calcification by regulating the expression of histone deacetylase 5 in high phosphate conditions ( Choe et al, 2020b ). CircSmoc1-2 attenuates vascular calcification by regulating the miR-874-3p/Adam19 axis ( Ryu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 ncRNAs can function as both positive and negative regulators of VC. 21 We recently reported that miR-134-5p induces VC by suppressing histone deacetylase 5, 22 and miR-27a-3p targets ATF3 to inhibit VC in vascular smooth muscle cells (VSMCs). 23 In addition, we found that the lncRNA Lrrc75a-as1 works as a negative mediator of VC and inhibits osteoblast-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…VSMCs were cultured in Dulbecco's modi ed Eagle's medium (DMEM) containing 10% FBS, and 1% penicillin-streptomycin at 37°C with 5% CO 2 . To induce calci cation, VSMCs at passage 3 were treated with 10 mM β-glycerophosphate (Sigma, St Louis, MO, USA) for total six days as previously reported (6). After washing with PBS for twice, the quanti cation of calcium deposition was evaluated by using Alizarin Red staining.…”
Section: Cell Isolation Culture and Construction Of Calci Cation Modelmentioning
confidence: 99%
“…A large number of miRNAs have been identi ed to participate in the metabolic process of calcium deposition, and potentially acted as e cient predictors for vascular calci cation. For example, miR-134-5p induces calcium deposition by inhibiting the expression of histone deacetylase 5 in VSMCs (6). MiR-135a has been demonstrated to suppress the calci cation in senescent VSMCs by modulating KLF4/STAT3 signaling pathway (7).…”
Section: Introductionmentioning
confidence: 99%